Ekonomi Perwakafan - Ajub Ishak (Al-Mizan (e-Journal), 2021)
This paper aims to examine waqf from an economic point of view. Land waqf as one of the economic instruments with social dimensions and is a logical consequence of the system of thought in Islam. Waqf entering the territory of the economic system can be understood if it is accompanied by a study of the economic paradigm, which leads to benefit. The approach used is a socio-economic approach, by looking at the importance of studies from an economic perspective on waqf, because waqf is essentially taking the benefits of productive waqf assets. Waqf has a solution contribution to social economic problems. Social understanding should be instilled on an ongoing basis, that property is not enough to be owned and controlled alone, but also to be enjoyed together. The distribution of wealth so that it can be enjoyed by others is through waqf and proper and proper management. Economically, waqf land that meets the requirements to be developed is in a strategic location, can be developed and will certainly produce, of course preceded by a careful study through an economic paradigm approach to make it happen. Its embodiment is based on waqf regulations that provide encouragement and motivation to optimize waqf goals, especially economic goals.